Reionización por jets de núcleos galácticos activos - Garate Núñez, Lucía Paz (2021)
The nature of the sources responsible for the reionization of the universe is still uncertain. Dwarf galaxies, through their intense ultraviolet flux are considered as the main candidates. Recent works propose the active galactic nuclei with jets as additional sources of the late reionization (at redshift z ≈ 6). These sources would inject ionizing photons into the intergalactic medium through inverse Compton scattering of relativistic electrons off photons from the cosmic microwave background. Energetic considerations suggest that this input is significant. However, a precise knowledge of the spectral signatures is required to compute the ionizing power accurately. In this work we present preliminary results of Monte Carlo simulations that were used to compute the steady-state scattered photon spectrum. We find that essentially all the power from the electron population is deposited in ionizing photons.